The American Society of Magical Negroes [videorecording (Blu-Ray)] - Libii, Kobi, 1980-; Smith, Justice, 1995-; Grier, David Alan, 1956 June 30-; Bogan, An-Li; Tarver, Drew, 1986-; Watkins, Michaela, 1971-; Hinds, Aisha, 1975-; Baltz, Tim; Friend, Rupert; Byer, Nicole (Universal, 2024)
The American Society of Magical Negroes is a fresh, satirical comedy about a young man, Aren, who is recruited into a secret society of magical Black people who dedicate their lives to a cause of utmost importance: making white people's lives easier.